2004
DOI: 10.1159/000078568
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the mouse <i>Arht2</i> gene which encodes a putative atypical GTPase

Abstract: ARHT is a new subgroup of the Rho family identified recently, which consists of two Rho-like genes, Arht1 and Arht2. ARHT may be involved in mitochondrial homeostasis and apoptosis. Constitutively active mutants of ARHT1 induced an aggregation of the mitochondrial network and resulted in an increased apoptotic rate of the cells. Here we report the molecular cloning and characterization of a novel mouse cDNA encoding a putative atypical GTPase protein, Arht2. Mouse Arht2 consists of 19 exons and has been mapped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…In humans, both Miro1 and Miro2 appear to be universally expressed, demonstrating particularly high expression levels in heart and skeletal muscle tissues [19]. The expression profile analysis of the mouse Miro2 ortholog, ARHT2, showed that ARHT2 is ubiquitously expressed throughout adult tissues, with high expression in heart, testis, skeletal muscle and brain, and lower expression in liver, lung and spleen [28]. The fact that the Miro GTPases are conserved from yeast to human, and are expressed in most cell types, suggest that these proteins have an essential role in organism development and cell survival.…”
Section: The Miro Gtpasesmentioning
confidence: 99%
“…In humans, both Miro1 and Miro2 appear to be universally expressed, demonstrating particularly high expression levels in heart and skeletal muscle tissues [19]. The expression profile analysis of the mouse Miro2 ortholog, ARHT2, showed that ARHT2 is ubiquitously expressed throughout adult tissues, with high expression in heart, testis, skeletal muscle and brain, and lower expression in liver, lung and spleen [28]. The fact that the Miro GTPases are conserved from yeast to human, and are expressed in most cell types, suggest that these proteins have an essential role in organism development and cell survival.…”
Section: The Miro Gtpasesmentioning
confidence: 99%
“…A novel class of GTPases, the Miro GTPase family, was recently identified in humans (Fransson et al, 2003(Fransson et al, , 2006, mice (Shan et al, 2004), yeast (Frederick et al, 2004), and Drosophila (Guo et al, 2005). They contain two GTPase domains and two calcium binding EF-hand motifs and are associated with the outer mitochondrial membrane via their C-terminal transmembrane domains (TMs) ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%